2020
DOI: 10.1590/1980-57642020dn14-040014
|View full text |Cite
|
Sign up to set email alerts
|

Cerebral toxoplasmosis and alcohol abuse in AIDS: dementia with multiple etiologies

Abstract: Major neurocognitive disorder due to multiple etiologies, or dementia due to multiple etiologies (DME), is a term coined by the Diagnostic and Statistical Manual of Mental Disorders to refer to complex cases when multiple pathologies, such as Alzheimer's disease, Lewy Bodies, human immunodeficiency virus (HIV), vascular-related brain damage or frontotemporal lobar degeneration, are identified as contributing to neurocognitive impairment and/or behavioral alterations, based on patient's neuroimaging tests, labo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…A case study found that clindamycin treatment provided clinical improvement within 48 h of treatment and resolved irregular brain lesions in the right basal ganglia within 3 weeks of treatment [73]. Another case study proposed clindamycin to be used to improve the cognitive function of AIDS patients with cerebral toxoplasmosis and alcohol abuse [74][75][76]. Thus, the use of clindamycin can be extended to patients with PTSD and ASUD.…”
Section: Effect Of Medication Use On Ptsd For Asud Predictionmentioning
confidence: 99%
“…A case study found that clindamycin treatment provided clinical improvement within 48 h of treatment and resolved irregular brain lesions in the right basal ganglia within 3 weeks of treatment [73]. Another case study proposed clindamycin to be used to improve the cognitive function of AIDS patients with cerebral toxoplasmosis and alcohol abuse [74][75][76]. Thus, the use of clindamycin can be extended to patients with PTSD and ASUD.…”
Section: Effect Of Medication Use On Ptsd For Asud Predictionmentioning
confidence: 99%
“…A case study found, clindamycin treatment provided clinical improvement within 48 hours of treatment and resolved irregular brain lesions in the right basal ganglia within 3 weeks of treatment 74 . Another case study, proposed clindamycin to be used to improve cognitive function of AIDS patients with cerebral toxoplasmosis and alcohol abuse [75][76][77] . Thus, the use of clindamycin can be extended to patients with PTSD and ASUD.…”
Section: Clindamycinmentioning
confidence: 99%